PENGEMBANGAN BISNIS SOSIAL DARI PENGELOLAAN LIMBAH RUMAH TANGGA UNTUK PENGENTASAN KEMISKINAN DI JATI PULO, JAKARTA BARAT - Syarief Darmoyo; Rakhdiny Sustaningrum; Susy Y.R. Sanie-Herman (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2019)
A Poverty and healthy life style are part of social problems and become global concern. By cooperating with Jatipulo subdistrict on RW 08 in West Jakarta, lectures and students held the Organic Composing Fertilizer and Marketing Training. The training involved local housewives, local youth committee, and some head of RT. The aims of the activity were to manage the house waste (wasted rice, vegetables) to be processed into organic fertilizer and expected to help the locals and to reduce the house waste by selling the organic composing fertilizer combines with ornamental-plant. There were 60 participants in total attending the training. The training was held on October 14 and November 13 2018 with the evaluation afterwards. The training method was presenting the demonstration and hands-on practical to understand deeply. Te result of evaluation were organic compos successfully implemented and the pot was produced with the current trend design in order to attract millennial customers.